(untitled) (Homiletic, 2015)
Postcolonial criticism has made its way into the field of religion mostly in the disciplines of theology and biblical studies. Little has been done to approach liturgics and homiletics from a postcolonial perspective. Building on such initial approaches, this paper recovers the tradition of the Taíno religion—the pre-Columbian religion in the Antilles prior to colonial times—and borrows from it a worldview of “complementary dualities” and a ritual pattern that embraces both conflict and unity. Drawing on the tradition of the Taíno religion and building on the work of postcolonial theologians, this paper proposes a liturgical dynamic that moves the community from spaces of tension to experiences of connectedness in order to alleviate the segregation of colonized and colonizers.